Prevalence of anemia and associated factors among pregnant women in Southern Ethiopia: A community based cross-sectional study - Lebso, Meaza; Anato, Anchamo; Loha, Eskindir (PLOS ONE, 2017)
Background Anemia is defined as a condition in which there is less than the normal hemoglobin (Hb) level in the body. During pregnancy; iron deficiency is associated with multiple adverse outcomes for both mother and infant. Most of the studies conducted in Ethiopia on anemia during pregnancy were conducted at institution level and associated factors are not well studied and documented. Independent factors like, food security status, dietary diversity and intestinal parasites infection were considered by only a few of them. Hence, the aim of this study was to determine the prevalence of anemia and associated factors among pregnant women in Lemo District, Southern Ethiopia. Methods Community based cross- sectional study was conducted from May-June 2015. Multistage sampling was used to include 507 study participants. Anaemia was diagnosed using HemoCue HB 301 and haemoglobin concentration <11 g/dl was classified as anaemic. Stool examinations were also done. Structured questionnaire was used as a tool to collect sociodemographic characteristics, individual dietary diversity and level of household food security data. Multivariate logistic regression model was employed to determine the effect of explanatory variables like level of education, level of household food security, dietary diversity, trimester of pregnancy, family planning before pregnancy, deworming, gravidity, iron intake in current pregnancy and soil transmitted helminthes on dependent variable anemia. Results The prevalence of anemia was 23.2% (95% CI: 19.5%-26.9%). Factors associated with anemia were: low socio-economic status (AOR = 2.03, 95% CI: 1.11–3.69), trimester second (AOR = 3.09, 95%CI: 1.41–6.79) and third (AOR = 3.68, 95% CI: 1.67–8.08), gravidity three to five (AOR = 1.78, 95% CI: 1.03–3.07) and six and above (AOR = 2.59, 95%CI: 1.37–4.92), not supplemented with iron (AOR = 1.72, 95% CI: 1.02–2.91), low dietary diversity score (AOR = 3.18, 95% CI: 1.37–7.37) and hookworm infection (AOR = 2.69, 95%CI: 1.34–5.39). Conclusion Anemia has moderate public health significance in the area. Community-based interventions should be enhanced considering the identified associated factors.